Growth Rate Differences of Chrysomya sp. Larvae on Rattus novergicus Wistar Strain Corpse Exposed and Unexposed to Ephedrine Toxic Dose - Poeranto, Sri; Prastowo, Wening; Resmi, Diandra Laksmita; Nugraha, Rivo Yudhinata Brian (Journal of Tropical Life Science, 2017)
Post Mortem Interval (PMI) is used as a parameter to define the onset, cause, manner, and time of death to help maintenance of law and identify crime victims by the age of the larvae found. Larval growth is influenced by the temperature, humidity, and contaminant (drug or toxic). This experiment used two media of dead rats (200 grams), one given ephedrine of LD50 = 266 mg/kg and the other without ephedrine. Both were put in 2 cages each containing 50 Chrysomya sp. Ten larvae were randomly taken every day for 14 days to be measured their length, weight, and duration of growth. The 3rd larvae stage in the media with ephedrine had weight gain on 5th – 6th day morning, while larvae in media without ephedrine had static weight gain on 5th day morning - afternoon and weight decrement on 6 – 7th day morning. Larva’s peak ratio of length/weight in the media with ephedrine was higher than that of larvae in the media without ephedrine. Larvae on media with ephedrine grew faster in 1st, 2nd, 3rd larvae stage, and pupal stage compared to larvae without ephedrine. Therefore, this study indicates that ephedrine can accelerate the growth rate of Chrysomya sp. larvae.